The role of microRNAs and nanoparticles in ovarian cancer: a review. (5th November 2018) - Kafshdooz, Leila; Pourfathi, Hojjat; Akbarzadeh, Abolfazl; Kafshdooz, Taiebeh; Razban, Zohre; Sheervalilou, Roghayeh; Ebrahimi Sadr, Naser; Khalilov, Rovshan; Saghfi, Siamak; Kavetskyy, Taras; Mammadova, Lala; Mehrizadeh, Masoud; et al.
Abstract: MicroRNAs (miRNAs) have had a revolutionary impact on cancer research over the recent years. They emerge as important players in tumourigenesis, leading to a paradigm shift in oncology. Ovarian cancer is the leading cause of death among gynaecologic malignancies. Therefore, there is a strong need for prognostic and predictive markers for early diagnosis which helps optimize and personalize treatment. Asymptomatically, ovarian cancer is often diagnosed at advanced and incurable stages. Efficient targeting and sustained release of miRNAs/anti-miRNAs using nanoparticles conjugated with antibodies and/or peptides could reduce the required therapeutic dosage while minimizing systemic and cellular toxicity. Given miRNAs importance in clinical oncology, here we focus on the development of miRNA nanoformulations to achieve enhanced cellular uptake, bioavailability and accumulation at the tumour site. Although many obstacles need to be overcome, miRNA therapy could be a powerful tool for ovarian cancer prevention and treatment. In this review, we discuss about the emerging roles of miRNAs in various aspects of ovarian cancer.